2004
DOI: 10.1016/j.jcrs.2004.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Flap thickness accuracy

Abstract: The results demonstrated variability between the 6 microkeratome models. Device labeling did not necessarily represent the mean flap thickness obtained, nor was it uniform or consistent. Thinner corneas were associated with thinner flaps and thicker corneas with thicker flaps. In addition, first cuts were generally associated with thicker flaps when compared to second cuts in bilateral procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…1,2 The terms thick-flap LASIK and thin-flap LASIK have arisen to describe traditional microkeratome flaps (mean thickness approximately 150 μm 3 ) and those created with newer microkeratomes or a femtosecond laser (mean thickness approximately 100 μm 1,2,46 ), respectively.…”
mentioning
confidence: 99%
“…1,2 The terms thick-flap LASIK and thin-flap LASIK have arisen to describe traditional microkeratome flaps (mean thickness approximately 150 μm 3 ) and those created with newer microkeratomes or a femtosecond laser (mean thickness approximately 100 μm 1,2,46 ), respectively.…”
mentioning
confidence: 99%
“…Many different studies1429 found significant variations in the flap thickness created by different types of mechanical microkeratomes. Solomon et al14 compared six models of microkeratomes (AMO Amadeus, Bausch and Lomb Hansatome, Moria Carriazo-Barraquer, Moria M2, Nidek MK2000, and Alcon Summit Krumeich-Barraquer) in a large prospective, multicenter study and found that the Amadeus 140 and the Nidek MK2000 145 produced the most consistent LASIK flap thicknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Solomon et al14 compared six models of microkeratomes (AMO Amadeus, Bausch and Lomb Hansatome, Moria Carriazo-Barraquer, Moria M2, Nidek MK2000, and Alcon Summit Krumeich-Barraquer) in a large prospective, multicenter study and found that the Amadeus 140 and the Nidek MK2000 145 produced the most consistent LASIK flap thicknesses. They reported that the current microkeratomes have a reliable performance and show SDs in flap thickness between 15 and 35 µm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Adverse events associated with the use of NSAIDs include keratitis, corneal subepithelial infiltrates, ulceration, and corneal melt. [14][15][16] Forty percent (40%) of subjects participating in clinical trials reported transient stinging and burning on instillation (U.S. Food & Drug Administration [FDA] safety sheet data) of 0.5% ketorolac. A reduced concentration of ketorolac would possibly diminish patient complaints of stinging and burning after its instillation.…”
Section: Introduction K Etorolac Tromethamine Is a Nonsteroidalmentioning
confidence: 99%